Extent of neck dissection after transoral robotic surgical resection of oropharyngeal squamous cell carcinoma: Report of a case and potential indications for inclusion of level I in a selective neck dissection. Issue 10 (26th June 2015) - Noel, Christopher W.; Foreman, Andrew; Goldstein, David P.; de Almeida, John R.
ABSTRACT: Background: With new minimally invasive surgical techniques playing a role in the management of early oropharyngeal carcinomas, appropriate surgical management of the neck is an increasingly important consideration. Methods: We present a case of a 47‐year‐old patient with a clinical T2N1M0 squamous cell carcinoma (SCC) of the right tonsil with anterior extension toward the floor of the mouth from the right glossotonsillar sulcus. Imaging revealed a solitary necrotic lymph node in level IIA. The decision was made to proceed with a transoral robotic pharyngectomy and selective neck dissection of levels II to IV, followed by adjuvant radiotherapy. Results: A postoperative scan revealed progressive regional disease in the anterior aspect of level IB, and, as such, a completion neck dissection of level I was performed. Conclusion: Special consideration must be given to level I, particularly in patients with glossotonsillar sulcus involvement and anterior extension toward the floor of the mouth. © 2015 Wiley Periodicals, Inc. Head Neck 37: E130–E133, 2015